Management of chronic myeloid leukaemia: current treatment options, challenges, and future strategies. Issue 1 (31st December 2023) - Younes, Salma; Ismail, Mohamed A.; Al-Jurf, Rana; Ziyada, Ayah; Nasrallah, Gheyath K.; Abdulrouf, Palli Valapila; Nagy, Mohamed; Zayed, Hatem; Farrell, Thomas; Sorio, Claudio; Morsi, Hisham; Qoronfleh, M. Walid; et al.
ABSTRACT : Small molecule therapy is a critical component of targeted anticancer treatment, with tyrosine kinase inhibitors (TKIs) being the first compounds to treat the clonal Chronic Myelogenous Leukaemia (CML) translocation t (9;22) (q34; q11) effectively since 2001. TKIs, such as imatinib, have improved the 10-year survival rate of CML patients to 80%. They bind the BCR::ABL1 kinase and inhibit downstream signaling pathways. However, therapy failure may be seen in 20-25% of CML patients due to intolerance or inadequacy related to BCR::ABL1 dependent or independent mechanisms. This review aimed to summarize current treatment options involving TKIs, resistance mechanisms and the prospective approaches to overcome TKI resistance. We highlight BCR::ABL1 -dependent mechanisms of TKI resistance by reviewing clinically-documented BCR::ABL1 mutations and their consequences for TKI binding. In addition, we summarize BCR::ABL1 independent pathways, including the relevance of drug efflux, dysregulation of microRNA, and the involvement of alternative signaling pathways. We also discuss future approaches, such as gene-editing techniques in the context of CML, as potential therapeutic strategies.